Сім’я в осмисленні католицьких мас-медіа незалежної України: жанрово-тематичні особливості публікацій - Керц, Ольга І.; Kerts, О. І. (Волинський національний університет імені Лесі Українки, 2012)
Розглянуто підходи римо-католицьких мас-медіа України до висвітлення питань сім'ї як важливого аспекту соціальної проблематики, ідейно-концептуальні засади публікацій, жанрові характеристики. The peculiarities of family problems (an important aspect of social issues) as performed by the Catholic mass-media in Ukraine, ideological and conceptual foundations of publication, genre characteristics are explored.
Family in the Comprehension of the Catholic Mass-Media of Iindependent Ukraine: Genre-Thematic Features of Publications
Keywords: мас-медіа; mass media; Римо-Католицька Церква; Roman Catholic Church; сім’я; family; тематика; subject; жанр; genre